Hydrogen sulfide inhalation ameliorates allergen induced airway hypereactivity by modulating mast cell activation. (October 2015) - Roviezzo, Fiorentina; Bertolino, Antonio; Sorrentino, Rosalinda; Terlizzi, Michela; Matteis, Maria; Calderone, Vincenzo; Mattera, Valentina; Martelli, Alma; Spaziano, Giuseppe; Pinto, Aldo; D'Agostino, Bruno; Cirino, Giuseppe
Graphical abstract: Abstract: Compelling evidence suggests that hydrogen sulfide represents an important gaseous transmitter in the mammalian respiratory system. In the present study, we have evaluated the role of mast cells in hydrogen sulfide-induced effects on airways in a mouse model of asthma. Mice were sensitized to ovalbumin and received aerosol of a hydrogen sulfide donor (NaHS; 100 ppm) starting at day 7 after ovalbumin challenge. Exposure to hydrogen sulfide abrogated ovalbumin-induced bronchial hypereactivity as well as the increase in lung resistance. Concomitantly, hydrogen sulfide prevented mast cell activity as well as FGF-2 and IL-13 upregulation. Conversely, pulmonary inflammation and the increase in plasmatic IgE levels were not affected by hydrogen sulfide. A lack of hydrogen sulfide effects in mast cell deficient mice occurred. Primary fibroblasts harvested from ovalbumin-sensitized mice showed an increased proliferation rate that was inhibited by hydrogen sulfide aerosol. Furthermore, ovalbumin-induced transdifferentiation of pulmonary fibroblasts into myofibroblasts was reversed. Finally, hydrogen sulfide did abrogate in vitro the degranulation of the mast cell-like RBL-2H3 cell line. Similarly to the in vivo experiments the inhibitory effect was present only when the cells were activated by antigen exposure. In conclusion, inhaled hydrogen sulfide improves lung function and inhibits bronchial hyper-reactivity by modulating mast cells and in turn fibroblast activation.